2004
DOI: 10.1002/lsm.20029
|View full text |Cite
|
Sign up to set email alerts
|

Laser cartilage reshaping in an in vivo rabbit model using a 1.54 μm Er:Glass laser

Abstract: Rabbit ear cartilage can be reshaped with an Er:Glass laser. This technique could offer exciting possibilities that may help patients whose cartilage-lined joints have been affected by disease or trauma. This technique could be certainly utilized to correct alar cartilage deformities and septum deviation of cleft lips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 33 publications
2
76
0
Order By: Relevance
“…Experimental results [6,55] indicate the conditions for in vivo laser reshaping are different from those found in vitro. Furthermore, histological examination of ear cartilage undergoing laser reshaping indicates a new cartilage of hyaline type replaces the old partially damaged irradiated cartilage of elastic type.…”
Section: Animal Studies Of Laser Reshaping Of Cartilagementioning
confidence: 89%
“…Experimental results [6,55] indicate the conditions for in vivo laser reshaping are different from those found in vitro. Furthermore, histological examination of ear cartilage undergoing laser reshaping indicates a new cartilage of hyaline type replaces the old partially damaged irradiated cartilage of elastic type.…”
Section: Animal Studies Of Laser Reshaping Of Cartilagementioning
confidence: 89%
“…Recently, Mordon et al [4] have demonstrated that rabbit ear cartilage can be reshaped in situ with an Er:Glass laser (1.54 mm). The possibility of obtaining a permanent reshaping of rabbit ear with no skin incision and no skin perforation was especially impressive since it is usually considered that rabbit ear are not a suitable model because the rabbit ear is supported by muscles that are far more substantial than those of humans [5].…”
mentioning
confidence: 99%
“…However, further studies will have to look into this. Over expression of HSP following laser irradiation has been well documented in the fields of dermatology, ophthalmology and more recently in cartilage reshaping [13,14,[46][47][48]. In fact, some HSP were identified in bone through immunolocalization in a paper by Tiffee et al [49].…”
Section: Discussionmentioning
confidence: 99%